Development and Thermal Requirements of Abaris basistriata (Coleoptera: Carabidae) Under Laboratory Conditions - Araújo Wanderley, Maria José; Cividanes, Francisco Jorge; PEREIRA DA Costa-Menezes, NIVÂNIA; SOARES DE Matos, SIDNÉIA TEREZINHA [UNESP]; DE SOUZA Ferraz, RENER LUCIANO (SAGE Publications, 2024)
The carabid beetle Abaris basistriata (Coleoptera: Carabidae) is noteworthy for its predatory capabilities and its generalist function in the habitat. This study aimed to assess the influence of different temperatures on the development of A. basistriata and determine its thermal requirements. The insect was fed with larvae of Tenebrio molitor (Coleoptera: Tenebrionidae) and maintained at 18, 22, 25, and 28 ± 1 °C, 70 ± 10 % relative humidity, and 14-hour photoperiod. There were significant differences in the development time of stages and instars of A. basistriata as a function of temperature. Threshold temperatures for egg, larva, pupa, and preimaginal development were 10.68, 11.32, 12.67, and 11.73 °C, respectively. The thermal constants were 82.41, 264.83, 84.57, and 664.89 degree-days, respectively. The highest number of A. basistriata individuals reached the adult stage in the shortest time of development at 28 °C, where 70 % of survival was recorded. This finding suggests that 28 °C is the most favorable temperature for rearing this carabid species under laboratory conditions.
Desarrollo y exigencias térmicas de Abaris basistriata (Coleoptera: Carabidae) bajo condiciones de laboratorio
Keywords: Biological control; biology; ground beetle; predator; temperature; Tenebrio molitor